2009
DOI: 10.1177/0016986208330566
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Goal Orientations, Quality, and Stability in Gifted and Other Adolescents' Friendships

Abstract: Competitive goal orientations were rated by self, peers, and teachers for 38 gifted- and 38 regular-program, same-sex, friendship dyads (19 female and 19 male) from grades 7 and 8 (N = 152). Gifted dyads were reassessed on friendship quality and stability at the end of the school year and after the summer. Gifted students were more task-oriented and comparison students more other-referenced. Task-orientation was related to fewer friendship conflicts, more friendly competition, and, for gifted students, greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 45 publications
(52 reference statements)
1
25
0
Order By: Relevance
“…As for the assumption, that rivalry inevitably damages relationships, Schapiro et al (2009) questions the connection between competitiveness and its harm to friendship. In a Canadian study of 7 th and 8 th graders, competitiveness among 76 pairs of a gifted and non-gifted friends has been examined, and the results showed that while the aims of learning were different in the 2 groups, the gifted had learning goals and the non-gifted -achieving goals, competiveness did not have any influence on the friendship of these dyads of friends.…”
Section: Resultsmentioning
confidence: 99%
“…As for the assumption, that rivalry inevitably damages relationships, Schapiro et al (2009) questions the connection between competitiveness and its harm to friendship. In a Canadian study of 7 th and 8 th graders, competitiveness among 76 pairs of a gifted and non-gifted friends has been examined, and the results showed that while the aims of learning were different in the 2 groups, the gifted had learning goals and the non-gifted -achieving goals, competiveness did not have any influence on the friendship of these dyads of friends.…”
Section: Resultsmentioning
confidence: 99%
“…(Ash & Huebner, 1998, pp. 312-313) Ackerman (1997; Ash and Huebner (1998);Baker (1996); Dai (2001); Estell et al (2009); Gaultney (1998); Hannah and Shore (1995); Hawkins (1997); Jausovec (1996); Jausovec (1997); Klein and Zehms (1996); Maksic (1997); Metha and McWhirter (1997);Muj et al (2000); Park, Park, and Choe (2005); Rovan and Vlahovic-Stetic (2008); Schapiro et al (2009);Steiner (2006); Thornton et al (2006); Tirri and Nokelainen (2007); Tong and Yewchuk (1996); Wu and Elliott (2008) Identification method used Example Sources used…”
Section: Discussionmentioning
confidence: 99%
“…1) Ackerman (1997);Bain and Bell (2004);Baker (1996); L. K. S Chan (1996)Delcourt, Lyn, and Rejskind (1997);Gallucci et al (1999);Gaultney (1998);Gentry, Gable, and Springer (2000);George and Scheft (1998);Hannah and Shore (1995);Hawkins (1997);Heng (2000);Kher-durlabhji et al (1997);Klein and Zehms (1996);Liu et al (2008);McCoach and Siegle (2002); Mendez(2000);Merrell et al (1996);Mooij and Driessen (2008);Muj, Yeung, Low, and Jin (2000);Nail and Evans (1997);Parker and Mills (1996);Rigo et al (1998);Schapiro, Schneider, Shore, Margison, and Udvari (2009);Schommer and Walker (1997);…”
mentioning
confidence: 99%
“…Studies examining friendship qualities amongst high ability and gifted learners have yielded mixed results. For example, some have found high ability students report lower degrees of friendship intimacy (Mayseless, 1993) and fewer positive friendship qualities (i.e., companionship, help, security, closeness;Schapiro, Schneider, Shore, Margison, & Udvari, 2009) with a best friend than average ability peers. Yet other researchers have found gifted students viewed their friendships as more close and intimate than non-gifted peers (Field et al, 1998) and were more likely to report more positive friendship qualities (Masden, Leung, Shore, Schneider, and Udvari, 2015).…”
Section: High Ability or Giftednessmentioning
confidence: 99%
“…A language arts teacher completed the Teacher Competition Rating Scales (cognitive scales; Schneider et al, 2005) and the physical education teacher completed the physical scales. Data were collected at the end of the first semester of the school year, at the end of the school year, and at the start of the next school year (Schapiro et al, 2009).…”
Section: High Ability and Giftedmentioning
confidence: 99%